Tindak Pidana Illegal Mining Bagi Perusahaan Yang Melakukan Pertambangan Tanpa Izin - Jorico Lavianchandra; Alpi Sahari; Ahmad Fauzi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
The issuance of law number 4 of 2009 concerning mineral and coal mining provides a new authority in the world of the act does not close the gap of illegal mining which is rife in Indonesia. Although the law already exists, the fact is that mining without permits continues. This study aims to determine the forms of non-criminal illegal mining and accountability. Forms of illegal mining are criinal acts of mining without permission either UIP, IPR or IUPK. Criminal offenses submit false report data, criminal offenses of exploration without rights, criminal offenses as holders of UIP exploration without carrying out production operations activities, criminal acts of laundering mining goods, criminal offenses related to abuse of authority of the official of the licensing authority, criminal acts which is a legal entity. The criminal liability against companies that carry aut mining activities without a permit is by imprisonment and with a criminal fine. Besides that the leablity for companies that conduct mining with civi sanctions and also administrative sanctions by way of making a business.